Periodic Boundary Value Problems for the Second Order Impulsive Differential Equations - Thaiprayoon, Chatthai; Tariboon, Jessada; Khumsup, Preya (Communications in Mathematics and Applications, 2010)
This paper is concerned with solutions of periodic boundary value problems for the second order impulsive differential equation. We prove the existence of extreme solutions and present the method of lower and upper solutions coupled with monotone iterative technique. Some comparison results are also established.